Enhanced Capacitive Properties of Manganese Dioxide Nanowires Coating with Polyaniline by in situ Polymerization. Issue 1659 (4th February 2014) - Wu, Lihao; Li, Yingzhi; Yu, Pingping; Zhang, Qinghua
ABSTRACT: Among the transition metal oxides, manganese oxides have been widely studied for electrochemical capacitors and batteries, because of their high energy density, low cost, natural abundance and environmentally friendliness. However, the poor electrical conductivity of manganese dioxide (MnO2 ) limits its capacitive response. Polyaniline becomes a unique and promising conducting polymer with a great potential application in supercapacitors due to easy synthesis and good conductivity of the conducting material. Combine the two properties can prepare nanocomposite materials in order to improve the conductivity and capacitive performance of the MnO2 . MnO2 coated with polyaniline as the coaxial nanowires were prepared in this report. The polyaniline was synthesized via in situ polymerization and we got a controllable thin coating on the well-dispersed MnO2 nanowires. This hybrid nanostructure enhances the conductivity and capacitive performance of the supercapacitor electrode. The specific capacitance of MnO2 /PANI composites is as high as 426 F g -1 at 1 A g -1, which is twice much higher than pure MnO2 (188 F g -1 ) .